2011
DOI: 10.1557/jmr.2010.51
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of effective thermal conductivities of woven fabric composites using unit cells at multiple length scales

Abstract: A procedure for predicting the in-plane and out-of-plane thermal conductivities of woven fabric composites through a combined approach of the representative volume element method and heat transfer analyses via finite element is presented. The representative volume element method was implemented using two unit cells established at different length scales with periodic boundary conditions. The procedure was exemplified on a plain weave glass fabric reinforced epoxy resin matrix composite. Sensitivity studies wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 10 publications
0
28
0
Order By: Relevance
“…The two unit cells have been systematically derived and presented in our previous work. 24,25 A micrograph of a polished transverse section from the plainweave composite is shown in Fig. 3.…”
Section: Displacement Fields Of All Unit Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…The two unit cells have been systematically derived and presented in our previous work. 24,25 A micrograph of a polished transverse section from the plainweave composite is shown in Fig. 3.…”
Section: Displacement Fields Of All Unit Cellsmentioning
confidence: 99%
“…The volume of unit cell 2 is 14.14 mm 3 . 24,25 It has been observed that a typical composite specimen possesses between 2 and 5% void volume fraction. 23 The void volume fraction of voids in unit cell 2 is assumed to be 5% and the radius of a void is assumed to be 25-55 µm.…”
Section: Displacement Fields Of All Unit Cellsmentioning
confidence: 99%
“…In particular, considerable attention was paid to the calculation of effective thermal conductivity of composites using the finite element method (FEM) [1][2][3]. For example, Islam and Pramila [1] studied the thermal conductivity of periodic fiber reinforced composites using FEM and considered four different boundary conditions on the boundary of RVE.…”
Section: Introductionmentioning
confidence: 99%
“…square and hexagonal ones, by FEM. Li et al [3] employed the finite element technique implemented by the commercial software ABAQUS to solve the hexagon RVE for determining the effective thermal conductivity of woven fabric composites. Usually, the implementation of FEM to simulate fiber or particle filled composites with high inclusion volume fraction results in an extremely large number of elements in the vicinity of the material interface in order to obtain an acceptable accuracy, due to restriction of element connectivity and the requirement of an appropriate value of element aspect ratio.…”
Section: Introductionmentioning
confidence: 99%
“…The determination of effective properties of composite materials is of paramount importance in engineering design and application of composite materials. The effective thermal conductivity and other thermo-physical properties of composites have attracted considerable interest in theoretical, numerical and experimental researchers during the last several decades (Brennan and Walrath 2009;Chen and Cheng 1967;Farooqi and Sheikh 2006;Kachanov and Sevostianov 2005;Landis et al 2000;Li et al 2011;Tsukrov and Novak 2002). It is expected to save much effort, time and expense if the properties of the new reinforced composites could be predicted accurately or designed from micro-structural properties of its constituents.…”
Section: Introductionmentioning
confidence: 99%